2016
DOI: 10.1007/s13593-016-0351-4
|View full text |Cite
|
Sign up to set email alerts
|

Novel resistance mechanisms of a wild tomato against the glasshouse whitefly

Abstract: The glasshouse whitefly, Trialeurodes vaporariorum, is an important pest of many crop plants including tomato, Solanum lycopersicum. Many wild tomato species exhibit a higher resistance to whiteflies. Therefore, locating the source of this enhanced resistance and breeding it into commercial tomato species is an important strategy to reduce the impact of pests on crops. Here, we assessed the pest resistance of Lycopersicon pimpinellifolium by comparing oviposition and feeding data from T. vaporariorum on this w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 44 publications
1
16
0
1
Order By: Relevance
“…In recent times, whitefly resistance traits have been reported in wild tomato relatives with red fruits and more closely related to cultivated tomato that can facilitate their use. Thus, whitefly resistance was found in Solanum galapagense S. Darwin and Peralta and Solanum pimpinellifolium L. [25,31,33,46,47]. Interestingly, the traits found in S. galapagense involved in resistance to whiteflies were associated with the presence of type IV leaf glandular trichomes and the acylsugars they produce [41].…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, whitefly resistance traits have been reported in wild tomato relatives with red fruits and more closely related to cultivated tomato that can facilitate their use. Thus, whitefly resistance was found in Solanum galapagense S. Darwin and Peralta and Solanum pimpinellifolium L. [25,31,33,46,47]. Interestingly, the traits found in S. galapagense involved in resistance to whiteflies were associated with the presence of type IV leaf glandular trichomes and the acylsugars they produce [41].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that the majority (31/41-75.6%) of whitefly EPG studies were performed well after the recommendation to use the platinum wire tethering protocol (Walker and Janssen 2000), we found that 26/31 published studies still used 10-12.5 μm diameter gold wire as the tethering material (Table 1). Additionally, among (Lei et al 1996) Adults (Lei et al 1997(Lei et al , 1998(Lei et al , 1999(Lei et al , 2001 12.5 T. vaporariorum Adults (Janssen et al 1989;Tosh and Brogan 2014;McDaniel et al 2016) those studies using 2.5 μm platinum wire, quantitative data are not available on the frequencies and durations of various stylet activities because platinum wire studies focused on waveform descriptions rather than replicated experimental sessions (Table 1). Thus, it is not possible to directly determine how the choice of wiring material influences the results obtained from EPG studies with whiteflies.…”
Section: Introductionmentioning
confidence: 99%
“…The whitefly is an important insect pest of many crop plants, including tomato. Many wild tomato species contains Mi gene, which provides resistance to whitefly (McDaniel et al, 2016). The wild tomato (S. peruvianum) resistance gene Mi encodes a protein with CC-NBS-LRR motifs (Milligan et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Tomato (Solanum lycopersicum L.) is an important vegetable crop and it is produced worldwide under both the glasshouse and open field (Kaur et al, 2014;McDaniel et al, 2016;Alatar et al, 2017). Whitefly (Bemisia tabaci) of Aleyrodidae family (Order: Hemiptera), is among the most harmful insects of tomato and causes significant yield loss.…”
Section: Introductionmentioning
confidence: 99%